Integrating Edublog in the teaching of narrative writing in primary school - Nur Nadiya Baharuddin,; Maslawati Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The Malaysia Education Blueprint 2013-2025 aims to optimize the use of Information and Communication Technology (ICT) in enhancing teaching and learning (T&L). Edublogs could be a useful platform that can facilitate the T&L of English. This case study explored the effects of the teaching of English narrative writing using Edublogs on pupils’ achievement in narrative writing in terms of content, vocabulary, and grammar. Eight Year 6 pupils were purposely selected as participants. Data was collected using focus group interviews, observation, and tests. Data were analysed using thematic analysis and document analysis. Findings show that learning narrative writing using Edublogs significantly improved the pupils’ ability to generate better content and improved the pupils’ vocabulary development and retention. However, the pupils were found to show no significant improvement in terms of grammar. The findings implicate that Edublogs can help in providing a meaningful T&L of language in the 21st century learning environment. It is suggested that future similar research using other digital applications and tools to be done with other language skills namely, reading, speaking, or listening. In addition, a longer duration of the similar study could also be considered in order to allow the natural course of learning to take place for grammar competence.